Microcirculatory Impairment Is Associated With Multiple Organ Dysfunction Following Traumatic Hemorrhagic Shock: The MICROSHOCK Study. Issue 9 (September 2018) - Hutchings, Sam D.; Naumann, David N.; Hopkins, Philip; Mellis, Clare; Riozzi, Paul; Sartini, Stefano; Mamuza, Jasna; Harris, Tim; Midwinter, Mark J.; Wendon, Julia
Abstract : Objectives: To assess the relationship between microcirculatory perfusion and multiple organ dysfunction syndrome in patients following traumatic hemorrhagic shock. Design: Multicenter prospective longitudinal observational study. Setting: Three U.K. major trauma centers. Patients: Fifty-eight intubated and ventilated patients with traumatic hemorrhagic shock. Interventions: Sublingual incident dark field microscopy was performed within 12 hours of ICU admission (D0) and repeated 24 and 48 hours later. Cardiac output was assessed using oesophageal Doppler. Multiple organ dysfunction syndrome was defined as Serial Organ Failure Assessment score greater than or equal to 6 at day 7 post injury. Measurements and Main Results: Data from 58 patients were analyzed. Patients had a mean age of 43 ± 19 years, Injury Severity Score of 29 ± 14, and initial lactate of 7.3 ± 6.1 mmol/L and received 6 U (interquartile range, 4–11 U) of packed RBCs during initial resuscitation. Compared with patients without multiple organ dysfunction syndrome at day 7, patients with multiple organ dysfunction syndrome had lower D0 perfused vessel density (11.2 ± 1.8 and 8.6 ± 1.8 mm/mm 2 ; p < 0.01) and microcirculatory flow index (2.8 [2.6–2.9] and 2.6 [2.2–2.8]; p < 0.01) but similar cardiac index (2.5 [± 0.6] and 2.1 [± 0.7] L/min//m 2 ; p = 0.11). Perfused vessel density demonstrated the best discrimination for predicting subsequent multiple organ dysfunction syndrome (area under curve 0.87 [0.76–0.99]) compared with highest recorded lactate (area under curve 0.69 [0.53–0.84]), cardiac index (area under curve 0.66 [0.49–0.83]) and lowest recorded systolic blood pressure (area under curve 0.54 [0.39–0.70]). Conclusions: Microcirculatory hypoperfusion immediately following traumatic hemorrhagic shock and resuscitation is associated with increased multiple organ dysfunction syndrome. Microcirculatory variables are better prognostic indicators for the development of multiple organ dysfunction syndrome than more traditional indices. Microcirculatory perfusion is a potential endpoint of resuscitation following traumatic hemorrhagic shock. Abstract : Supplemental Digital Content is available in the text.